Controlling O coverage and stability by alloying Au and Ag. Issue 38 (19th September 2016) - Montemore, Matthew M.; Cubuk, Ekin D.; Klobas, J. Eric; Schmid, Martin; Madix, Robert J.; Friend, Cynthia M.; Kaxiras, Efthimios
Abstract : Alloying Au into Ag(110) reduces the O coverage and stability in a well-controlled manner. Abstract : One of the most critical factors in oxidation catalysis is controlling the state of oxygen on the surface. Au and Ag are both effective selective oxidation catalysts for various reactions, and their interactions with oxygen are critical for determining their catalytic performance. Here, we show that the state of oxygen on a catalytic surface can be controlled by alloying Au and Ag. Using temperature programmed desorption, density functional theory (DFT), and Monte Carlo simulations, we examine how alloying Au into an Ag(110) surface affects O2 dissociation, O coverage, and O stability. DFT calculations indicate that Au resides in the second layer, in agreement with previous experimental findings. The minimum ensemble size for O2 dissociation is 2 Ag atoms in adjacent rows of the second layer. Surprisingly, adsorbed O2 and the dissociation transition state interact directly with metal atoms in the adjacent trough, such that Au in this position inhibits O2 dissociation by direct repulsion with oxygen electronic states. Using Monte Carlo simulations based on DFT energetics, we create models of the surface that agree closely with our experimental results. Both show that the O2 uptake decreases nearly linearly as the Au concentration increases, and no O2 uptake occurs for Au concentrations above 50%. For Au concentrations greater than 18%, increasing the Au concentration also decreases the stability of the adsorbed O. Based on these results, the O coverage and O stability can be tuned, in some cases independently. We also study how the reactivity of the surface is affected by these factors using CO2 oxidation as a simple test reaction.